2021
DOI: 10.1007/s00234-021-02816-6
|View full text |Cite
|
Sign up to set email alerts
|

Radiation exposure in the endovascular therapy of cranial and spinal dural arteriovenous fistula in the last decade: a retrospective, single-center observational study

Abstract: Purpose This study aims to determine local diagnostic reference levels (DRLs) in the endovascular therapy (EVT) of patients with cranial and spinal dural arteriovenous fistula (dAVF). Methods In a retrospective study design, DRLs and achievable dose (AD) were assessed for all patients with cranial and spinal dAVF undergoing EVT (I) or diagnostic angiography (II). All procedures were performed at the flat-panel angiography-system Allura Xper (Philips Health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…Recently, Opitz et al suggested a DRL for spinal angiographies performed in patients presenting with SDAVF. They presented dosimetric data for SDAVFs from 58 diagnostic spinal angiographies, revealing a DRL of 396.39 Gy cm 2 [18], which is in line with our calculated values. Furthermore, two multicenter studies from France done by Etard et al and Kien et al reported DRLs for spinal angiographies [19,20].…”
Section: Resultssupporting
confidence: 88%
“…Recently, Opitz et al suggested a DRL for spinal angiographies performed in patients presenting with SDAVF. They presented dosimetric data for SDAVFs from 58 diagnostic spinal angiographies, revealing a DRL of 396.39 Gy cm 2 [18], which is in line with our calculated values. Furthermore, two multicenter studies from France done by Etard et al and Kien et al reported DRLs for spinal angiographies [19,20].…”
Section: Resultssupporting
confidence: 88%
“…Only in a few dosimetry studies, have intracranial DAFVs been represented as a subcategory [ 14 , 21 , 22 ]. The reported results in terms of local DRLs were quite various (414 Gy cm 2 , 507.33 Gy cm 2 and 730 Gy cm 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…The reported results in terms of local DRLs were quite various (414 Gy cm 2 , 507.33 Gy cm 2 and 730 Gy cm 2 ). However, Forbrig et al [ 14 ] and Opitz et al [ 21 ] excluded CCFs, and Kien et al [ 22 ] did not describe the inclusion criteria in detail. Regarding FT, Forbrig et al, proposed 142 min and Kien et al, 80 min.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported on radiation exposure and FT during neurointerventional procedures with modern biplane angiography systems, e.g., mechanical thrombectomy [ 20 , 21 ] and endovascular treatment of intracranial dural arteriovenous fistulae [ 22 , 23 ] or carotid-cavernous fistula [ 24 ]. The aim is to raise awareness of the radiation dose and, in the long term, to optimize the modification of angiography systems and therapeutic techniques.…”
Section: Discussionmentioning
confidence: 99%